Genetically Modified Organisms : Specifics of Doing Business in the European Union. - Medunová, Tereza (2018)
Adoption of GM crops brought important changes to the agricultural sector. Since its commercialization in 1996, genetic modification has become a discussed topic. Given the different approaches towards the regulation of GM food in the world, the business environment may be considered as sensitive, uncertain and highly restricted, especially in the European Union. The European precautionary approach subjects the GMOs to strict and long control process which restricts the business. The study is considered to be an empirical study arranged to examine the specifics of doing business with GMOs in the EU market and to identify its crucial limitation. Thus, this thesis calls for a deductive approach supported by the example of Monsanto with the focus on its activities in the European market. The research based on reviewing literature, scientific articles, journals and statistical data concluded, that there are several specifics in the attitude towards GMOs within the EU such as the strict approval process, traceability and labelling policy, national policies of single member states, the customer attitude and increasing monopolization of the industry.